2019
DOI: 10.1108/jmlc-03-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Implementation evaluation: a future direction in money laundering investigation

Abstract: Purpose Malaysia has implemented a comprehensive AML/CFT framework, yet its effectiveness remains questionable due to low number of prosecutions on money laundering cases. Therefore, this study aims to understand the reasons for low number of prosecutions, by addressing the challenges faced by the law enforcement agencies in conducting money laundering investigation. This study then identifies future improvement actions to enhance their effectiveness in combating money laundering in future. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Money laundering crimes that extend beyond tax evasion include drug and human trafficking, trade and insurance fraud, prostitution, various illegal profit-motivated crimes derived from banks, securities, arms smuggling, gambling, extortion and terrorism (Irwin et al , 2012). As such, the complex nature of money laundering has become challenging to the law enforcement agencies and relevant authorities in prosecuting money laundering offences (Zolkaflil et al , 2019). Even though money laundering and terrorism financing prosecutions remain low in Malaysia, only 132 of 821 cases were prosecuted, whilst 54 cases remain ongoing (FATF, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Money laundering crimes that extend beyond tax evasion include drug and human trafficking, trade and insurance fraud, prostitution, various illegal profit-motivated crimes derived from banks, securities, arms smuggling, gambling, extortion and terrorism (Irwin et al , 2012). As such, the complex nature of money laundering has become challenging to the law enforcement agencies and relevant authorities in prosecuting money laundering offences (Zolkaflil et al , 2019). Even though money laundering and terrorism financing prosecutions remain low in Malaysia, only 132 of 821 cases were prosecuted, whilst 54 cases remain ongoing (FATF, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign governments sometimes do not see the request for assistance as valid in their legal context because they do not know the exact fact that the request is legitimate and the relevant differences that exist between the requested country’s legal system and the requester’s. The foreign governments can also see foreign demand as a direct threat to their sovereignty (Hinterseer, 2002; Zolkaflil et al , 2019). Moreover, law enforcement is part of the sovereign right of the state for violations that occur in its territory.…”
Section: Limits Of Territorial Jurisdiction To Overcome Cross-border ...mentioning
confidence: 99%
“…Zolkafil et al (2019) revealed that although the law enforcement agencies have the power to investigate money laundering and terrorism financing under the act, Malaysia is lacking in having a good investigative support system to assist the law enforcement agencies during the investigation process. Aurasu and Rahman (2016) concluded that anti-money laundering laws can be improved by being a better and established civil forfeiture regime where Malaysia will be able to discharge its duties well on forfeiting benefits from criminals.…”
Section: Money Launderingmentioning
confidence: 99%